Impact of Family-Centered Early Intervention in Infants with Autism Spectrum Disorder: A Single-Subject Design - Ho Il Park; Hae Yean Park; Eunyoung Yoo; Areum Han (Occupational Therapy International)
Objective. Autism spectrum disorder is a neurodevelopmental disorder that affects communication, social skills, and behavior and can present in early childhood. The present study is aimed at investigating the effects of family-centered early intervention on the quality of social interaction and social interaction skills in infants with suspected autism spectrum disorder using a single-subject design. Method. As a single-subject design study, evaluations were conducted at baseline phase A, intervention phase B, baseline phase A′, and follow-up phase. The family-centered early intervention program was implemented during the intervention phase. Family-centered early intervention programs included home environmental modification, play video recording and training, task and feedback, related information training, and question and answer. The Modified Checklist for Autism in Toddlers, Revised, with Follow-Up and Evaluation of Social Interaction was used for evaluation. Result. Three participants completed the study. After applying the family-centered early intervention program, the quality of social interaction and social interaction skills of all participants improved. In addition, the risk of autism spectrum disorder in all participants was reduced. Conclusion. Family-centered early intervention was confirmed to have a positive effect on the improvement of social interaction skills in infants with suspected autism spectrum disorder.